THERAPEUTIC EFFICACY OF ALLIUM SATIVUM AGAINST SLEEP DEPRIVATION-INDUCED DYSLIPIDEMIA IN ADULT FEMALE WISTAR RATS - Malgwi, Ibrahim Samaila; Muhammad, Abdulmalik; Emmanuel, Nachamada Solomon; Yusuf, Anas Husainy; Yakubu, Godwin H. (FUDMA JOURNAL OF SCIENCES, 2025)
Sleep deprivation (SD) resulting from unhealthy lifestyle choices poses oxidative challenges and is strongly linked to an increased risk and prevalence of various metabolic disorders. While the negative effects of SD on mental health are well documented, its impact on lipid metabolism remains less explored. Allium sativum (Garlic) has been recognized for its cardioprotective properties in different preclinical models. This study aimed to investigate the cumulative effects of acute SD on lipid metabolism and assess the potential therapeutic benefits of aqueous A. sativum extract using female Wistar rats as the experimental model. The animals (N = 25) were categorized into five groups of five animals each (n = 5): Group I served as the normal control and was administered distilled water (1ml/kg), whereas Group II represented the negative control (sleep-deprived, untreated). Groups III, IV, and V received oral administration of A. sativum extract at doses of 100, 200, and 400 mg/kg, respectively, over three weeks. The study analyzed plasma lipid profiles following treatment and found significant reductions in total cholesterol (T. CHOL), triglycerides (TG), and low-density lipoprotein (LDL) across most treated groups. In contrast, high-density lipoprotein (HDL) levels increased, particularly in treated groups compared to Group II. The decrease in TG and LDL was statistically significant (P 0.05), while HDL showed a notable rise. These results suggest that Allium sativum extract may help regulate lipid metabolism and offer protective benefits against cardiovascular diseases and atherosclerosis. However, the limitation of the study is that the acute SD model may...